Turning a Blind Eye to African Refugees and Immigrants in a Tourist City: A Case-study of Blame-shifting in Cape Town - Ruiters, Greg; Lombard, Felicia; Uwimpuhwe, Denys (African Human Mobility Review, 2021)
What role do municipalities play in limiting xenophobia in all its forms and whatshould these bodies do in promoting the integration of African immigrants? This paperanalyzes a case study of Cape Town’s policies and programs concerning African immigrantsand refugees following the 2008 xenophobic crisis, up to 2016. Municipalitiesas a separate sphere of the government have their own space to address socio-politicalproblems and to shape local alliances and urban life. Despite being a tourist-led, gentrifyingcity which substantially draws on vulnerable African immigrant labor, CapeTown’s leaders and businesses, however, have no explicit policies or programs to addressxenophobia – a ticking time bomb; and they tend to shift the blame to otheractors. City leaders and employers see African immigrants in an instrumental way (asmere labor; a financial burden and not as potential citizens). This paper focuses on localgovernment’s definition of the ‘foreign immigrant problem’ and its poor record ofreducing the drivers of xenophobic conflicts in South African cities, recognizing thatwhile cities are not the only players, they certainly are the closest to the problem. Thepaper concludes that the city needs a proactive, comprehensive approach, recognizingmigrants and their organizations, especially foreign workers, legal immigrants andrefugees, as key city builders, stakeholders and potential citizens in the city. The paperdraws on interviews with city officials, migrants and asylum seekers in the City of CapeTown.